Vendor Managed Inventory Practices: A Case in Manufacturing Companies - Kamaruddin Radzuan; Mohd Faizal Omar; Mohd Nasrun Mohd Nawi; Irwan Abdul Rahim; Mazri Yaakob (International Journal of Supply Chain Management, 2018)
The implementation of the Vendor Managed Inventory (VMI) in the Malaysian manufacturing sector can be viewed as a solution to mitigate the increment of operational costs and low performance in customer services. Many factors contributed to the performance of the VMI programme, but only a few attempts was made to determine the contribution of the VMI elements on VMI performance. The objectives of this study were to investigate the level of VMI practices, organizational factors and VMI performance; and to examine the influence of type of product on VMI element and VMI performance. The study used qualitative approach, which data were gathered from semi-structured questions through interview process. There are 4 manufacturing companies listed in the Federation of Malaysian Manufacturers were selected for data collection purpose. The findings showed that high information sharing, moderate level of inventory control, close inventory location to customer premises, inventory ownership, mutual decision on inventory replenishment are among VMI practices in manufacturing companies. The respondents also confirmed that the influence of type of product characteristic onto VMI performance only to a limited extent. As a recommendation, supplier and customer must design their VMI program, which suit to product characteristics. Another important part is VMI agreement should be balanced between the need of suppliers authority in controlling customers inventory and current capability of supplier. They should consider the flexibility of VMI system, especially the capability to reduce cost on behalf of the supplier and to provide better service to the customer.